2015
DOI: 10.1016/j.jacep.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Sports Participation in Genotype Positive Children with Long QT Syndrome

Abstract: OBJECTIVE-The study sought to examine the prevalence and outcomes of sports participation (both competitive and recreational) in our single-center LQTS genotype positive pediatric population. BACKGROUND-The risks of sports participation in patients with long QT syndrome (LQTS)are not clearly elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…A prospective study from Italy found a 73% mortality reduction in athletes from early detection of hypertrophic cardiomyopathy compared to unscreened non-athletes 51. In addition, individualised management and indepth counseling of children diagnosed with long QT syndrome have shown low cardiac event rates and no deaths in two separate cohorts of young recreational and competitive athletes 99 100. Expert consensus guidelines for risk stratification and management of asymptomatic athletes identified with a Wolff-Parkinson-White pattern also were developed in partnership between the Pediatric and Congenital Electrophysiology Society and the Heart Rhythm Society 101 102.…”
Section: Outcomes For Early Detection Of Cardiovascular Diseasementioning
confidence: 99%
“…A prospective study from Italy found a 73% mortality reduction in athletes from early detection of hypertrophic cardiomyopathy compared to unscreened non-athletes 51. In addition, individualised management and indepth counseling of children diagnosed with long QT syndrome have shown low cardiac event rates and no deaths in two separate cohorts of young recreational and competitive athletes 99 100. Expert consensus guidelines for risk stratification and management of asymptomatic athletes identified with a Wolff-Parkinson-White pattern also were developed in partnership between the Pediatric and Congenital Electrophysiology Society and the Heart Rhythm Society 101 102.…”
Section: Outcomes For Early Detection Of Cardiovascular Diseasementioning
confidence: 99%
“…Even though the new American scientific statement [14] is more liberal regarding channelopathies and supports participation under certain conditions, on the bases of recent findings [15,16], the 2005 ESC recommendations [9] advise that these individuals should not be involved in competitive sports or should be excluded from most competitive sports, with the possibility of those of low intensity sports (Classification of sports is based on Mitchell et al [17]). …”
Section: To Disqualify or Not To Disqualify?mentioning
confidence: 99%
“…For example, large cohort studies using current therapeutic measures have demonstrated improved survival and low mortality rates in children and young adults with hypertrophic cardiomyopathy 16 17. For children diagnosed with long QT syndrome, individualised management and in-depth counselling were associated with low cardiac event rates and no deaths in two independent cohorts of young athletes 18 19. For asymptomatic athletes identified with ventricular pre-excitation (Wolff-Parkinson-White pattern), expert consensus guidelines define risk stratification and management strategies to reduce risk 20 21.…”
Section: Disease-oriented Outcomes Evidencementioning
confidence: 99%